Hox dosage contributes to flight appendage morphology in Drosophila - Paul, Rachel; Giraud, Guillaume; Domsch, Katrin; Duffraisse, Marilyne; Marmigère, Frédéric; Khan, Soumen; Vanderperre, Solene; Lohmann, Ingrid; Stoks, Robby; Shashidhara, L. S.; Merabet, Samir (Nature Communications, 2021)
Flying insects have invaded all the aerial space on Earth and this astonishing radiation could not have been possible without a remarkable morphological diversification of their flight appendages. Here, we show that characteristic spatial expression profiles and levels of the Hox genes Antennapedia (Antp) and Ultrabithorax (Ubx) underlie the formation of two different flight organs in the fruit fly Drosophila melanogaster. We further demonstrate that flight appendage morphology is dependent on specific Hox doses. Interestingly, we find that wing morphology from evolutionary distant four-winged insect species is also associated with a differential expression of Antp and Ubx. We propose that variation in the spatial expression profile and dosage of Hox proteins is a major determinant of flight appendage diversification in Drosophila and possibly in other insect species during evolution.